2012
DOI: 10.4217/opr.2012.34.3.305
|View full text |Cite
|
Sign up to set email alerts
|

Ocean Response to the Pinatubo and 1259 Volcanic Eruptions

Abstract: : The ocean's response to the Pinatubo and 1259 volcanic eruptions was investigated using an ocean general circulation model equipped with an energy balance model. Volcanic eruptions release gases into the atmosphere which increases the aerosol optical depth and acts to reduce the incoming short-wave radiation. For example, there was a huge volcanic eruption (Pinatubo) in 1991 which reduced the global mean radiative forcing by about 3 W m −2 . Two numerical experiments were simulated. The first experiment feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 55 publications
6
14
0
Order By: Relevance
“…The volcanic forcing occurred irregularly and the range between the maximum and minimum volcanic forcing is quite large at approximately 40 W/m 2 . For example, the largest volcanic forcing occurred 1259 Samalas eruption in Indonesia (Lavigne et al 2013), which is seven times larger than the scale of the Pinatubo volcanic forcing in 1991 (Kim and Kim 2012). Table 1 summarizes years when volcanic eruptions occurred.…”
Section: Resultsmentioning
confidence: 97%
“…The volcanic forcing occurred irregularly and the range between the maximum and minimum volcanic forcing is quite large at approximately 40 W/m 2 . For example, the largest volcanic forcing occurred 1259 Samalas eruption in Indonesia (Lavigne et al 2013), which is seven times larger than the scale of the Pinatubo volcanic forcing in 1991 (Kim and Kim 2012). Table 1 summarizes years when volcanic eruptions occurred.…”
Section: Resultsmentioning
confidence: 97%
“…Yr +1 (red asterisks) displays the largest response to volcanism, fact that agrees with other studies accounting for the different averaged regions (Stenchikov et al, 2009;Balmaseda et al, 2013;Ding et al, 2014). Kim and Kim (2012) simulation results depict the largest cooling in the second year after the eruption (Yr +2). Contrary to Mignot et al (2011) for the North Atlantic Ocean and Church et al (2005) in the global average, that have observed a faster response, with surface temperatures decrease in the year of the eruption (Yr 0).…”
Section: Zonal Averagesupporting
confidence: 89%
“…SST at Yr +1 shows a cold anomaly peak of -0.6 ∘ C, that is in the range of Stenchikov et al (2009) simulation results between 1 and 0.4K. Fact that also agrees with Kim and Kim (2012) that have observed a cooling in their model results from 0.25 to 0.8 ∘ C, the higher limit is for LM eruptions. The same magnitude of a negative anomaly is present in two different regions, 30S and ∼55S (Figure 3.11a).…”
Section: Zonal Averagesupporting
confidence: 87%
See 2 more Smart Citations